Critical Discourse Analysis of Language and Power in EFL Classroom Interaction - Siti Amalia Rachmawati (Journal of English Teaching, 2022)
Abstract This study aims to discuss the use of language and the power possessed by the teacher in interacting with students in the classroom on the way student perceptions and its contribution to student learning outcomes. This study investigates teacher discourse and teacher-student discourse that occurs in the classroom interaction. Through this explanation of critical discourse analysis, the researcher proposes to distribute the concepts of classroom interaction between teacher and students, the use of the teacher’s language, and the use of the teacher’s power. This explains the role of the power of using language in classroom interactions to create good learning characteristics and outcomes. The analysis of this research is based on the theory of discourse analysis which focuses on the topic of language taken from Fairclough's theory and the types of power by French and Raven (1959). The method used in this study is a descriptive qualitative research method that deals with data in the form of words from interviews and questionnaires. The results showed that the teacher’s language in classroom interaction is used not only to interact with the students but also to provide the materials and information, to give instruction, and to train the students’ skills. The power with the highest frequency of use produced by the teacher during the learning process is expert power, reward power, referent power, legitimate power and the last is coercive power. Keywords: Critical Discourse Analysis, Classroom Interaction, Language, Power